2018
DOI: 10.3389/fvets.2018.00027
|View full text |Cite
|
Sign up to set email alerts
|

Successful Application of the Gamma-Interferon Assay in a Bovine Tuberculosis Eradication Program: The French Bullfighting Herd Experience

Abstract: In the French Camargue region, where bovine tuberculosis had been enzootic for several years in bullfighting cattle herds, the gamma-interferon (IFN) assay was used since 2003 in parallel with the intradermal test in order to increase overall disease detection sensitivity in infected herds. This study presents the results of a field-evaluation of the assay during a 10-year period (2004–2014) of disease control and surveillance program and explores the particular pattern of IFN assay results in bullfight herds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…Many studies have stated that parallel testing using a combination of two different tests could improve Se of assays and accelerate the resolution of a TB outbreak (6,8,12,37). In this study, when the two kinds of tests were used as single, serial, or in parallel for reactors identified using several laboratory tests, the parallel screening showed the highest Se (86/91, 94.5%).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Many studies have stated that parallel testing using a combination of two different tests could improve Se of assays and accelerate the resolution of a TB outbreak (6,8,12,37). In this study, when the two kinds of tests were used as single, serial, or in parallel for reactors identified using several laboratory tests, the parallel screening showed the highest Se (86/91, 94.5%).…”
Section: Discussionmentioning
confidence: 71%
“…Samples for determining sensitivity (Se) of the assay were collected from cattle diagnosed as positive by the CFT from herds in regions with bTB outbreaks. In total, 120 cattle identified as M. bovis infected from tissues and/or identified by polymerase chain reaction (PCR) after detection of typical bTB lesions on gross/microscopic examination were considered as truly bTB-positive (11,12).…”
Section: Use Of the Ifn-γ Assaymentioning
confidence: 99%
“…The univariable survival analyses revealed that production type was associated with longer bTB breakdown durations: unsurprisingly, outbreaks in bullfighting herds were significantly longer compared to beef/fattening and dairy/mixed herds in agreement with previous studies conducted in a different region in Spain ( 39 ). Some tests may have differing performances depending on breed type, what could impact the time to recover OTF status ( 40 ): in this sense, both the skin test and the IFN-γ assay can have a lower performance in bullfighting cattle due to a combination of stress, difficulties for performing correctly the test due to the temper of the animals, and the lower response to tuberculins/decreased IFN-γ production, what could lead to a higher proportion of false-negative animals remaining in the herd and thus further contribute to the increased outbreak duration ( 15 , 41 ). In addition, bullfighting herds are extensively managed and therefore can have an increased risk of contact with infected wildlife ( 42 ), which could lead to frequent reinfections, thus increasing the length of the outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…When discussing the Se, Sp and efficacy for the detection of TB infected animals of the various tests, neither set of authors considered the source of the Tuberculin PPDs, avian, and bovine, the individual potency or the relative potencies of these PPDs, in the possible reasons for the differences in observed results of the test performances. Similarly, Keck et al (71) observed very low SIT positive rates during two screening campaigns where the use of the Bovigam ® assay was found to increase the sensitivity of TB detection by more than 30% over and above the SIT using the official bovine Tuberculin PPD and the effect of the different PPDs used was not discussed as a possible factor in the different Se observed (71).…”
Section: Discussionmentioning
confidence: 97%
“…Few, if any, studies discussing the sensitivity range, and comparing ante-mortem test outcomes in various countries or regions or over time consider differences in the manufacturer or potency of the tuberculin as critical to test Se and much of the more recent literature in particular, seems to assume that all tuberculins will perform equally whether in skin test or IFN-γ assay (48, 6771). For example, the 2012 EFSA scientific opinion states that the selection of the cattle populations, the bovine TB testing history of the cattle and the prevalence of environmental mycobacteria, may have influenced performance estimates in the surveillance population samples used in their latent class analysis, specifically mentioning the low sensitivity of the skin test in one dataset (68).…”
Section: Discussionmentioning
confidence: 99%